2010
DOI: 10.1128/aac.00316-10
|View full text |Cite
|
Sign up to set email alerts
|

Expression, Purification, and Characterization of Aspergillus fumigatus Sterol 14-α Demethylase (CYP51) Isoenzymes A and B

Abstract: Aspergillus fumigatus sterol 14-␣ demethylase (CYP51) isoenzymes A (AF51A) and B (AF51B) were expressed in Escherichia coli and purified. The dithionite-reduced CO-P450 complex for AF51A was unstable, rapidly denaturing to inactive P420, in marked contrast to AF51B, where the CO-P450 complex was stable. Type I substrate binding spectra were obtained with purified AF51B using lanosterol (K s The sterol pathways of eukaryotes are highly conserved and are part of a larger biosynthetic pathway that includes the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
84
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(91 citation statements)
references
References 40 publications
2
84
2
1
Order By: Relevance
“…L-Histidine was removed from the preparation by washing the enzyme with affinity chromatography medium using a 50-kDa-molecular-mass-cutoff Amicon Ultra-4 centrifugal filter (Millipore). Difference spectra were obtained by titrating affinity-purified ScErg11p6ϫHis and used to determine dissociation constant (K d ) values for the binding to the triazole drugs FLC and VCZ (30,31). Incremental additions of up to 7 l of triazole drug dissolved in dimethyl sulfoxide (DMSO) were added to a 0.5-ml sample of 1 M ScErg11p6ϫHis in affinity chromatography buffer in a 10-mm-pathlength cuvette.…”
Section: Methodsmentioning
confidence: 99%
“…L-Histidine was removed from the preparation by washing the enzyme with affinity chromatography medium using a 50-kDa-molecular-mass-cutoff Amicon Ultra-4 centrifugal filter (Millipore). Difference spectra were obtained by titrating affinity-purified ScErg11p6ϫHis and used to determine dissociation constant (K d ) values for the binding to the triazole drugs FLC and VCZ (30,31). Incremental additions of up to 7 l of triazole drug dissolved in dimethyl sulfoxide (DMSO) were added to a 0.5-ml sample of 1 M ScErg11p6ϫHis in affinity chromatography buffer in a 10-mm-pathlength cuvette.…”
Section: Methodsmentioning
confidence: 99%
“…A. fumigatus is intrinsically resistant to the commonly used azole fluconazole (148), and it was suggested that the specific azole binding properties of A. fumigatus cyp51A and cyp51B may result in the intrinsic fluconazole resistance of this species (618). In 1990, itraconazole became the first azole introduced for the treatment of aspergillosis (146).…”
Section: Aspergillus Fumigatus Drug Resistance: the Azolesmentioning
confidence: 99%
“…Disruption of the ergosterol biosynthesis pathway leads to increased membrane permeability and instability in the fungal cell, which is deleterious to cell growth and replication (6,9). The intrinsic resistance of A. fumigatus to FLC is possibly due to the differential FLC binding affinity to the Cyp51A and Cyp51B proteins (8,10).…”
mentioning
confidence: 99%